Recent Interpretation of Hebrews Chapters 3–4: Critical Issues and Scholarly Trends. (November 2016) - Docherty, Susan
Chapters 3–4 have emerged as key to much recent scholarly interpretation of the epistle to the Hebrews. This paper offers an evaluative review of major recent publications which treat this section of Hebrews, drawing out some common themes and recurring critical issues. The questions addressed in these studies have significant implications for an understanding of Hebrews more widely, as they impact on judgements about subjects such as the letter's structure and main message, the author's use of the Old Testament, and the religious and conceptual background to his thought.